1992
DOI: 10.1037/h0079363
|View full text |Cite
|
Sign up to set email alerts
|

Psychological responses of rescue workers: Fire fighters and trauma.

Abstract: The psychological responses of two groups of fire fighters were examined following the performance of rescue work. Four types of responses were reported: identification with the victims, feelings of helplessness and guilt, fear of the unknown, and physiological reactions. Stress was found to be mediated by availability of social support, type of leadership, level of training, and use of rituals. Implications of these findings for preventive intervention measures are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(127 citation statements)
references
References 27 publications
5
117
1
4
Order By: Relevance
“…In addition, Dowdall-Thomae et al (2009) presented a Peer Support Action Plan for several different intervention techniques as a coaching and support strategy in order to correct behaviours and keep the rescue workers at their optimum level of functioning and performance (problem-focused and seeking social support) [34]. Other authors also confirmed that (emotional) social support is a crucial measure to cope with job-related stress in emergency personnel [35][36][37].…”
Section: Discussionmentioning
confidence: 77%
“…In addition, Dowdall-Thomae et al (2009) presented a Peer Support Action Plan for several different intervention techniques as a coaching and support strategy in order to correct behaviours and keep the rescue workers at their optimum level of functioning and performance (problem-focused and seeking social support) [34]. Other authors also confirmed that (emotional) social support is a crucial measure to cope with job-related stress in emergency personnel [35][36][37].…”
Section: Discussionmentioning
confidence: 77%
“…Firefighters have unique preconditions to develop working relationships and emotional connections, and higher degrees of work cohesion have been found to be significantly associated with decreased anxiety during emergencies. Other positive effects are successful decision making, greater effectiveness in responding to emergencies, a greater ability to cope with post-emergency experiences, and increased psychological well-being (Beaton, Murphy, Johnson, Pike, & Cornell, 1998;Fullerton, McCarroll, Ursano, & Wright, 1992;Landen & Wang, 2010;North et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In many debriefing models, the use of a peer debriefer is seen as vital to the success of the process (Mitchell & Everly, 1995) Upon review of the literature, it appears that the majority of research in the area of peer support models to mitigate occupational stress has been in the emergency services discipline. Several studies have shown that through dialogue with colleagues and others, it is possible to cope with the effects of traumatic and/or difficult experiences (Dyregrov, Kristoffersen, & Gjestad, 1996;Fullerton, McCarroll, Ursano, & Wright, 1992;Jonsson & Segesten, 2003). Social support diminishes stress and makes it understandable, thus making it possible to cope with distressing events (Dyregrov & Mitchell, 1992;Jonsson & Segesten, 2003).…”
Section: Peer Support Debriefing As An Intervention To Mitigate Disenmentioning
confidence: 99%